Persepsi Followers pada Personal Branding Perempuan Berturban di Instagram: Studi Fenomenologi - Dyah Ajeng Rayi Pangestuti; Muhammad Adi Pribadi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
Social media has become a strategic space for individuals to construct and communicate their public identities. Instagram, as a dominant visual platform, enables users to present personal images through visual content, narratives, and interactions with audiences. In this context, personal branding is no longer limited to public figures but has increasingly developed among individual content creators. One notable phenomenon is the emergence of turbaned women who consistently build their personal branding on social media. The Instagram account @rossafarahadiba, known as Ocha, is widely recognized through the identity of “the turbaned woman,” which is continuously displayed across her content. The turban functions not only as a personal style but also as a distinguishing symbol that shapes followers’ perceptions of her identity. However, previous studies have predominantly examined personal branding from the creator’s perspective, while research focusing on followers’ perceptions particularly toward turbaned women remains limited. This study aims to understand how followers interpret the personal branding of a turbaned woman on Instagram. The research employs a qualitative approach using a phenomenological method. The research subjects are followers of @rossafarahadiba who have followed the account for at least 5–7 months and actively engage through comments, likes, or story replies. Data were collected through in-depth interviews, documentation, and literature review, with data validity ensured through source triangulation. Data analysis is based on four dimensions of personal branding: clarity, consistency, credibility, and visibility. Media sosial telah menjadi ruang strategis bagi individu untuk membangun dan mengomunikasikan identitas diri secara publik. Instagram, sebagai platform visual yang dominan, memungkinkan pengguna menampilkan citra personal melalui visual, narasi, dan interaksi dengan audiens. Dalam konteks ini, personal branding tidak hanya dimiliki oleh figur publik, tetapi juga berkembang di kalangan konten kreator individu. Salah satu fenomena yang menarik adalah kemunculan perempuan berturban yang membangun personal branding secara konsisten di media sosial. Akun Instagram @rossafarahadiba atau Ocha dikenal melalui identitas “si cewek berturban” yang ditampilkan secara berkelanjutan dalam kontennya. Turban tidak hanya berfungsi sebagai gaya personal, tetapi juga menjadi simbol pembeda yang membentuk persepsi followers terhadap dirinya. Namun, penelitian terdahulu lebih banyak membahas personal branding dari sudut pandang kreator, sementara kajian yang menempatkan persepsi followers khususnya terhadap perempuan berturban masih terbatas. Penelitian ini bertujuan untuk memahami bagaimana followers memaknai personal branding perempuan berturban di Instagram. Penelitian menggunakan pendekatan kualitatif dengan metode fenomenologi. Subjek penelitian adalah followers @rossafarahadiba yang telah mengikuti akun tersebut selama minimal 5–7 bulan dan aktif berinteraksi melalui komentar, likes, atau reply story. Teknik pengumpulan data dilakukan melalui wawancara mendalam, dokumentasi, dan studi pustaka, dengan keabsahan data diuji melalui triangulasi sumber. Analisis data menggunakan teori empat dimensi personal branding: clarity, consistency, credibility, dan visibility.